Pemicuan 5 Pilar Sanitasi Total Berbasis Masyarakat di Desa Bale - Bungawati, A; Djaafar, Tjitrowati; Gusman, Gusman; Amsal, Amsal; Maryam, Maryam; Arianty, Ros; Rianti, Nova; Saharudin, Saharudin (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
This community service activity was carried out to enhance the understanding and preparedness of the residents of Bale Village in implementing the five pillars of Community-Based Total Sanitation. The activity took place on 3-4 March 2026, targeting 35 residents of Bale Village. The methods employed included coordination with the village government, mapping sanitation issues, delivering material, facilitating discussion, demonstrating practical skills, developing residents' commitments, and evaluating through pre- and post-tests. The evaluation results showed an increase in the average overall score from 49.20 in the pre-test to 83.90 in the post-test, an increase of 34.70 points. The highest improvements were observed in household waste management by 43.20 points and household liquid waste management by 41.20 points. Understanding of stopping open defecation, handwashing with soap, and managing household drinking water and food also improved. This activity provided residents with the opportunity to recognise sanitation risks in their environment and to develop steps for improvement that can be implemented at the household level. Similar activities should be continued with family assistance and ongoing monitoring of residents' commitments to ensure that knowledge changes develop into sanitary habits.